Pengembangan Media Pembelajaran Berbasis Video Animasi pada Materi Tumbuhan Sumber Kehidupan di Bumi Kelas IV Sekolah Dasar - Indri Rahmawati; Muhammad Makki; Fitri Puji Astria (Mataram University, 2026)
This research aims to determine the validity and practicality of animated video-based learning media on the topic of Plants as Sources of Life on Earth for fourth-grade elementary school students. The research used the Research and Development (R&D) method with the ADDIE development model, consisting of analysis, design, development, implementation, and evaluation stages. The research was conducted at SD Negeri 1 Darek with five students in the small-group trial and fifteen students in the large-group trial. The instruments included material expert validation questionnaires, media expert validation questionnaires, student response questionnaires, and teacher response questionnaires. Data were analyzed using qualitative and quantitative descriptive analysis techniques. The results showed that the learning media obtained a media expert validity score of 90.83% and a material expert validity score of 96.58%, both categorized as very valid. The practicality test showed student response percentages of 90.62% in the small-group trial and 86.04% in the large-group trial, while the teacher response reached 92.5%, all categorized as very practical. Therefore, the animated video-based learning media met the criteria of being very valid and very practical, making it suitable for use in the learning process.